Public good or private good? The paradox of public and private ethics in the context of developing countries - Hellsten, Sirku; Larbi, George A. (2006)
This article questions the view that corruption is part of the features of collectivist cultures. Whilst acknowledging that there are cultural differences in ethical and social norms, it argues that corruption is more likely due to social and economic realities and the disconnection between societal values and the values of formal public institutions. Also the failing of public trust leads into communitarian solidarity-networks within a state, which strive for the common good of particular social collectives rather than the national public good. In designing strategies to improve ethics and control corruption in the public sector we need to understand the social and economic conditions under which public duty and the ethical standards required from them tend to compete with the private moral commitments and social obligations of officials. The article suggests using civic education to diffuse the values of public service, and the rights and obligations of citizenship more widely in society. - Reproduced.
Keywords: Ethics